Altered Smooth Muscle Cell Force Generation as a Driver of Thoracic Aortic Aneurysms and Dissections - Milewicz, Dianna M. (Arterioscler Thromb Vasc Biol, 2016)
The importance of maintaining contractile function in aortic smooth muscle cells (SMCs) is evident by the fact that heterozygous mutations in the major structural proteins or kinases controlling contraction lead to the formation of aneurysms of the ascending thoracic aorta that predispose to life-threatening aortic dissections. Force generation by SMC requires ATP-dependent cyclic interactions between filaments composed of SMC specific isoforms of α-actin (encoded by ACTA2) and myosin heavy chain (MYH11). ACTA2 and MYH11 mutations shown to disrupt this cyclic interaction predispose to thoracic aortic disease. Movement of the myosin motor domain is controlled by phosphorylation of the regulatory light chain (RLC) on the myosin filament, and loss-of-function mutations in the dedicated kinase for this phosphorylation, myosin light chain kinase (MYLK) also predispose to thoracic aortic disease. Finally, a mutation in the cGMP-activated protein kinase (PRKG1) results in constitutive activation of the kinase in the absence of cGMP, thus driving SMC relaxation in part through increased de-phosphorylation of the RLC, and predisposes to thoracic aortic disease. Furthermore, SMCs cannot generate force without connections to the extracellular matrix (ECM) through focal adhesions, and mutations in the major protein in the ECM, fibrillin-1, linking SMCs to the matrix also cause thoracic aortic disease in individuals with Marfan syndrome. Thus, disruption of the ability of the aortic SMC to generate force through the elastin-contractile units in response to pulsatile blood flow may be a primary driver for thoracic aortic aneurysms and dissections.